Salivary IL-1ß as an Objective Measure for Fatigue in Multiple Sclerosis? - Hanken, Katrin; Sander, Carina; Qaiser, Lara; Schlake, Hans-Peter; Kastrup, Andreas; Haupts, Michael; Eling, Paul; Hildebrandt, Helmut (Frontiers in Neurology, 2018)
Background: The causes of fatigue in multiple sclerosis (MS) and other inflammatory disorders are not well understood. One possible cause that might explain fatigue in inflammatory disorders appears to be the immunological process itself, triggering neural activity that is experienced as fatigue. Objectives: To investigate whether salivary IL-1ß concentration, associated with systemic inflammation, is related to subjective fatigue in MS. Methods: 116 MS patients (62 relapsing remitting MS, 54 secondary progressive MS) and 51 healthy controls participated in this study. Salivary concentration of IL-1ß was determined using a commercially available enzyme-linked immunosorbent assay (ELISA) kit. Fatigue was assessed using various fatigue scales. We compared IL-1ß concentration between groups and performed regression analyses to investigate which variables best predict fatigue scores. Results: We found that the IL-1ß concentration best predicts fatigue scores in relapsing remitting MS patients, even though the IL-1ß concentration did not differ significantly between relapsing remitting MS patients and healthy controls. Secondary progressive MS patients showed a somewhat elevated IL-1ß concentration compared to relapsing remitting MS patients and healthy controls. Furthermore, disease modifying treatment had a significant effect on the IL-1ß concentration, with treated patients showing a lower IL-1ß concentration than non-treated patients. Conclusions: The present study points to a significant relation between the proinflammatory cytokine IL-1ß and fatigue in relapsing remitting MS patients. It also suggests a potential effect of disease modifying treatment on the peripheral IL-1ß concentration.